Quality of Super Chilled Poultry Meat at Storage - Rathod, K.S.; Ambadkar, R. K.; Naveena, B. M. (Journal of Meat Science, 2017)
The breast meat upon exposure to super chilling (-1.5 to -2.5°C), chilled (4°C) and frozen (-18°C) temperatures up to 24 h were assessed separately for various quality attributes. The moisture content of super chilled meat (75.74+0.53) was significantly less than chilled meat (78.09+0.49). The protein content was higher in fresh meat (20.56+0.31) as compared to chilled (18.13+0.39) and super chilled meat (18.78+0.27) while fat content was not affected. The pH and water holding capacity (WHC) showed non-significant effect of cooling. There was significant (p
Keywords: Poultry meat; Super chilling; Storage; Quality